A note on elastic noise source localization. (April 2016) - Wahab, Abdul; Nawaz, Rab
The problem of reconstructing the spatial support of ambient noise sources from elastic wavefield boundary measurements using cross-correlation techniques is dealt with. It is demystified that the cross-correlation-based standard source localization functional in elastic media does not provide optimal refocusing due to different pressure and shear wave speeds. Then, a weighted functional is proposed to rectify the coupling artifacts. A numerical experiment is presented to substantiate the appositeness of the proposed functional.